Shaping the Future of Electric Vehicles: Smart, Sustainable and Wireless Solar-Powered Charging System for Electric Vehicles - Basit Ahmad; Mudassar Rafique; Engr. Shazia Feroz; Muhammad Imran Iqbal; Azka Anwar; Syed Tahseenullah (Dialogue Social Science Review (DSSR), 2025)
The adoption of electric vehicles (EVs) is rapidly increasing as a sustainable transportation solution. However, the accessibility and availability of charging infrastructure remain a significant concern, particularly in urban and remote areas. To address this challenge, our project proposes the development of a Solar Power Bank with Wireless Charging (SPB-WC) for Electric Vehicles, aimed at enhancing the convenience and sustainability of EV charging. The SPB-WC is a portable and self-contained charging solution that integrates solar panels, energy storage, and wireless charging technology. This project aims to provide a reliable, renewable, and on-the-go charging option for electric vehicle owners, promoting the wider adoption of clean energy transportation. This article present a strategic planning and innovative design of a solar-powered charging system tailored for electric vehicles (EVs), addressing the pressing issues of costly gasoline and detrimental emissions. The global presence of EVs is on a consistent ascent, attributed to both environmental concerns and the economic advantage they offer by significantly reducing transportation expenses compared to conventional fuel-powered vehicles. In this study, we propose a groundbreaking solution by conceptualizing an EV charging infrastructure that capitalizes on solar energy. Our approach eliminates the need for stationary charging stations, enabling continuous charging while the EV is in motion. This self-sustaining system is driven solely by solar power, obviating the requirement for additional energy sources. The construction of this infrastructure incorporates various components such as solar panels, batteries, transformers, regulator circuitry, copper coils, AC to DC converters, a controller, and an LCD. Thus, our technology showcases the feasibility of integrating solar-powered, wireless charging systems seamlessly into road networks, thereby revolutionizing the paradigm of EV charging infrastructure.